All‐trans‐retinoic acid ameliorates experimental allergic encephalomyelitis by affecting dendritic cell and monocyte development. Issue 4 (11th March 2013) - Zhan, Xiao‐Xia; Liu, Yu; Yang, Jin‐Feng; Wang, Guang‐You; Mu, Lili; Zhang, Tong‐Shuai; Xie, Xiao‐Li; Wang, Jing‐Hua; Liu, Yu‐Mei; Kong, Qing‐Fei; Li, Hu‐Lun; Sun, Bo
Summary Experimental allergic encephalomyelitis (EAE) can be induced in animal models by injecting the MOG35–55 peptide subcutaneously. Dendritic cells (DCs) that are located at the immunization site phagocytose the MOG35–55 peptide. These DCs mature and migrate into the nearest draining lymph nodes (dLNs), then present antigen, resulting in the activation of naive T cells. T helper type 1 (Th1) and Th17 cells are the primary cells involved in EAE progression. All‐trans‐retinoic acid (AT‐RA) has been shown to have beneficial effects on EAE progression; however, whether AT‐RA influences DC maturation or mediates other functions is unclear. In the present study, we showed that AT‐RA led to the down‐regulation of MHC class II, CD80 (B7‐1) and CD86 (B7‐2) expressed on the surface of DCs that were isolated from dLNs or spleen 3 days post‐immunization in an EAE model. Changes to DC function influenced Th1/Th17 subset polarization. Furthermore, the number of CD44+ monocytes (which might trigger EAE progression) was also significantly decreased in dLNs, spleen, subarachnoid space and the spinal cord parenchyma after AT‐RA treatment. These findings are the first to demonstrate that AT‐RA impairs the antigen‐presenting capacity of DCs, leading to down‐regulation of pathogenic Th1 and Th17 inflammatory cell responses and reducing EAE severity.